Faktor-Faktor yang Memengaruhi Keputusan Adopsi Benih Padi Varietas Rojolele Srinuk oleh Petani Kecamatan Delanggu Kabupaten Klaten - Hapsari, Dennys Tyas; Widiyanti, Emi; Rusdiyana, Eksa (Universitas Sebelas Maret, 2022)
Rojolele Srinuk rice is a new variety developed by the National Nuclear Energy Agency (BATAN) with improved characteristics compared to its progenitor, Rojolele. This study investigates the internal and external factors of farmers who adopt the Rojolele Srinuk rice seed variety and those who do not. This study employs quantitative methodology. This investigation was conducted in Delanggu Sub-district, Klaten Regency. All of the participants in this investigation were rice farmers from the Delanggu Sub-district. The number of 48 respondents was chosen purposefully or intentionally as the sample size. They utilized descriptive analysis and logistic regression for analysis. Results indicated that factors such as age, education, farming experience, the nature of innovation, communication channels, and the function of agricultural extension agents were significant in determining adoption. Education, the essence of creation, and the role of agricultural extension agents substantially influence adoption decisions.